If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + 3) = 12 Reorder the terms: -6(3 + x) = 12 (3 * -6 + x * -6) = 12 (-18 + -6x) = 12 Solving -18 + -6x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -6x = 12 + 18 Combine like terms: -18 + 18 = 0 0 + -6x = 12 + 18 -6x = 12 + 18 Combine like terms: 12 + 18 = 30 -6x = 30 Divide each side by '-6'. x = -5 Simplifying x = -5
| a-4a=2a | | 3h-4=h+2 | | y+5/11=3 | | 48=-3p | | 2(3+3x)-4=20 | | 7x^2+38x+15= | | 39=5g-9 | | 3(4x+2)=2(4x+50) | | 1-7x+3=-17 | | 45.3*6= | | 1000=2000*(1+x) | | -12-5+11+4-5-13=12 | | -5c+6=-29 | | 14=-(p-8)+2 | | 6x+3=4x-8 | | 1000=x*(1+0,45) | | 3(3a-5)=60 | | 7(1+4x)=147 | | 4z^2-12z+13=0 | | w-15=4 | | 0=1.5x+x^1 | | -1+(-1.5)= | | 6(2x+5)= | | -3(-4x+2)=18 | | 3(10-3x)=120 | | x+1/4=5/8 | | 10-4x=6x-90 | | 0=16t^2-24t-1 | | x-33/7=2/3 | | 0=16t^2+24t+1 | | -7+4=-35 | | 14-7x=40-21x |